AL-QUR’AN SEBAGAI SUMBER TEKSTUAL FILSAFAT ISLAM - Wardani, Wardani (Jurnal Studia Insania, 2013)
This article is intended to argue against those who say that the Islamic philosophy is really nothing more than thetrue ancient Greek philosophy that has been ?repacked? by Islam, and to prove that Islamic philosophy, whilebeing as a result of historical process of its adopting of Greek philosophy, is to large extent the own Muslimthinkers? thoughts by ?adapting? that philosophical tradition with Islamic doctrine. As the result, they havesought to compromise between rational and revealed truth. Therefore, it sees that Islamic philosophy is a attemptto interpret the Qur?an in the light of reason. By this way of argumentation, the author wishes to say that thebalanced view of the origin of Islamic philosophy, e.g. between the historical and textual roots or betweeninfluence and originality, must be recognized, so that we will have a holistic understanding of the existence ofthis philosophical tradition in Islam.